The new biologic drugs: which children with asthma should get what? - Hillson,K; Saglani,S; Bush,A (Pediatric Pulmonology, 2024)
Novel biologics (targeted antibody therapies) have revolutionized the management of severe childhood asthma. However, it is important that the right biologic is selected for the right patient, and understanding the evidence base for each biologic is crucial. Currently, four biologics (all monoclonal antibodies) are licensed in the UK for the treatment of children with severe asthma - omalizumab (Xolair), mepolizumab (Nucala), and dupilumab (Dupixent) in children aged 6 years and over; and tezepelumab (Tezspire), only in children aged 12 years and over. Tezepelumab is the only licensed biological that may be beneficial in severe asthma without evidence of Type 2 inflammation. All have a good safety profile but varying degrees of clinical efficacy in children, with wide variation in treatment responsiveness between individual patients. When selecting biologics for severe asthma, it is essential to remember the limitations of the current pediatric evidence. At present, there are no results from randomized, head-to-head trials of biologics in severe asthma. TREAT is an ongoing trial comparing omalizumab to mepolizumab and will be one of the first to provide such evidence. We must be especially aware of the dangers of extrapolating data from adults to children, because the pathophysiology and role of biomarkers may differ significantly from adult asthma. Given the current level of knowledge, even after treatment has been initiated, children should be regularly reviewed to determine the efficacy of treatment, side-effect profile and consideration of when treatment with the biologic should be discontinued.